Wide-angle polarization-insensitive transparency of a continuous opaque metal film for near-infrared light - Song, Zhengyong (2014)
Here we show that a continuous highly conducting metal film can be made transparent for wide-angle and polarization-insensitive incidence of near-infrared light by depositing periodic metal patches on top of the metal film. Based on the optimized computations, the whole system could suppress the reflection and enhance the transmission. This design of transparent metal film can be useful in applications, such as optoelectronic electrodes, solar cells, and micro-electronic displays, where both high electrical conductivity and high optical transmittance are desirable.